Higher normalized concentrations of tetracycline resistance found in ballast and harbor water compared to ocean water. (February 2020) - Gerhard, William A.; Gunsch, Claudia K.
Abstract: Although ballast water is a known vector for the global transport of microorganisms, the Ballast Water Management Convention only sets limits for indicator organisms and does not consider antibiotic resistance genes (ARGs). Herein, we examined the concentration of indicator organisms and prevalence of three ARGs ( sul 1, tet (M), and van A) in a total of 53 ballast, 21 harbor, and 8 ocean samples collected in Singapore, China, South Africa, and California. E. coli was found in significantly higher concentrations in ballast samples obtained in Singapore and China compared to South Africa (Singapore, p = 0.040) and California (Singapore, p < 0.001; China, p = 0.038). Harbor samples from China had significantly higher concentrations of E. coli than Singapore (p = 0.049) and California (p = 0.001). When compared to ocean samples, there were significantly higher concentrations of normalized tet (M) in ballast samples from California (p = 0.011) and Singapore (p = 0.019) and in harbor samples from California (p = 0.018), Singapore (p = 0.010), and South Africa (p = 0.008). These findings suggest that microbial loads significantly differ among ports. Furthermore, certain ARGs are enriched in ballast and harbor waters when compared to ocean water, which suggests that ballast waters have the potential to either transport higher concentrations of certain ARGs or that ballast tank conditions may exert selective pressure for some ARGs. Highlights: E. coli concentrations were higher in Singapore and China ballast samples. These findings suggest that microbial loads differ between ports. California and Singapore had higher tet M concentration in ballast than ocean water. California, Singapore, and China had higher tetM concentration in harbor than ocean. Some ARGs may be enriched in ballast, and ballast may be a vector for dispersion.